Assessment of climate change impacts on salinity intrusion in Hong-Thai Binh and Dong Nai river basins - Thai, Tran Hong; Van, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract. Climate change (CC) is a global problem that not only affects the developed countries but also the developing ones asVietnam.  With a coastal line of approximately 3,260 km,Vietnam is expected to be affected considerably by climate change including salinity intrusion. Through the assessment of impacts of climate change on water resource in Hong-Thai Binh and Dong Nai river basins which located in two key economic zones, in the paper a general picture of impacts of climate change on salinity intrusion in Vietnam is presented, where MIKE 11 was used for Hong – Thai Binh basin and HydroGIS for Dong Nai basin.  The study gives out some results of salinity intrusion in the two basins according to three climate change scenarios in three typical years: 2030, 2050, and 2100. Finally, both the short and long terms adaptation measures to salinity intrusion caused by climate change inVietnam are summarized. Keywords : Climate change, salinity intrusion, Hong-Thai Binh river, Dong Nai river.